Template chart detection for stoma telediagnosis - Szwoch, Mariusz; Zawiślak, Rafał; Granosik, Grzegorz; Mik-Wojtczak, Joanna; Mik, Michał (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents the concept of using color template charts for the needs of telemedicine, particularly telediagnosis of the stoma. Although the concept is not new, the current popularity and level of development of digital cameras, especially those embedded in smartphones, allow common and reliable remote advice on various medical problems, which can be very important in the case of limitations in a physical contact with a doctor.
Keywords: stoma; marker detection; telediagnosis; distortion correction